Envisioning women in world history - Clay, Catherine (McGraw-Hill Higher Education, 2009)
Part of McGraw-Hill's Explorations in World History series, this brief and accessible volume presents a comparative survey of the early history of women from a global perspective. Each chapter, which can be read independently of the others, examines the experiences of women in one of seven civilizations typically covered in an introductory world history text: pre-agricultural societies, the Ancient Mediterranean, Gupta India/Southeast Asia, Tang/Song China, Maya and Aztec cultures, early Islam through the Abbasid caliphate, and Europe in the Late Middle Ages. Within these cultures, the authors explore a variety of issues impacting the lives of females in pre-modern history, including the ideal woman, female life cycles, women's roles in work and economy, female sexuality and spirituality, and women and politics. The book's brevity makes it an excellent companion text for students in world history, women's history, introductory sociology and anthropology courses, and women’s studies courses.